Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© Ø¹Ù† ÙƒØªØ§Ø¨ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙÙ‘ Ø§Ù„Ø³Ø§Ø¯Ø³ Ø¨Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…Ø¹Ù„Ù…ÙŠÙ† ÙˆØ§Ù„Ù…Ø¹Ù„Ù…Ø§Øª ØªÙ…Ø¨Ø§ÙƒØ¨Ø±Ø§Ø³ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ Ø£Ù„ÙÙ‡ Ù…ØÙ…Ø¯ Ø¥Ù„ÙŠØ§Ø³ - Affandi, Masykur; Shiddiq, Jamaluddin (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2019)
This study aims to find out 1) how the material presentation model from the book "Ta’lim al-Lughah al-ʻArabiyyah" by M. Ilyas, and 2) how the repetition model in the book. This study uses a qualitative approach with a type of library research and content analysis. The results of this study are (1) that the presentation of material in the book "Ta'lim al-Lughah al-'Arabiyyah" to sixth grade students at the Muta'allimiin Tambakberas Jombang school written by Mohamed Ilyas is seen very well with the introduction of publishers, book writers, table of contents, and all aspects that must be according to Maki in presenting the Material. In fact there are several aspects of the presentation of articles that have not been fulfilled, such as guides, bibliography, and glossary of terms. (2) In the field of review, this aspect can be considered good. in fact, but there are some that have to be reevaluated where they do not yet exist, such as the history of the author, motto, song, and so on. So, it would be better if it was added with a variety of exercises and additional lessons